A novel 3780-point FFT processor scheme for the time domain synchronous OFDM system - Leng, Ji-nan; Xie, Lei; Chen, Hui-fang; Wang, Kuang (Frontiers of information technology & electronic engineering, 2011)
The 3780-point FFT is a main component of the time domain synchronous OFDM （TDS-OFDM） system and the key technology in the Chinese Digital Multimedia/TV Broadcasting-Terrestrial （DMB-T） national standard. Sinc, e 3780 is not a power of 2, the classical radix-2 or radix-4 FFT algorithm cannot be applied directly. Hence, the Winograd Fourier transform algorithm （WFTA） and the Good-Thomas prime factor algorithm （PFA） are used to implement the 3780-point FFT processor. However, the structure based on WFTA and PFA has a large computational complexity and requires many DSPs in hardware implementation. In this paper, a novel 3780-point FFT processor scheme is proposed, in which a 60x63 iterative WFTA architecture with different mapping methods is imported to replace the PFA architecture, and an optimized CoOrdinate Rotation Digital Computer （CORDIC） module is used for the twiddle factor multiplications. Compared to the traditional scheme, our proposed 3780-point FFT processor scheme reduces the number of multiplications by 45% at the cost of 1% increase in the number of additions. All DSPs are replaced by the optimized CORDIC module and ROM. Simulation results show that the proposed 3780-point FFT processing scheme satisfies the requirement of the DMB-T standard, and is an efficient architecture for the TDS-OFDM system.